2019
DOI: 10.1017/s1355617719000328
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Expressive Suppression is Associated with Lapses in Instrumental Activities of Daily Living Among Community-Dwelling Older Adults

Abstract: Objectives: Expressive suppression (i.e., effortful regulation of overt affect) has a deleterious impact on executive functioning (EF). This relationship has potential ramifications for daily functioning, especially among older adults, because a close relationship exists between EF and functional independence. However, past research has not directly examined whether expressive suppression impacts instrumental activities of daily living (IADL). The present study examined this association among older adults. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…In the present study, accuracy was negatively impacted by high variability in daily busyness, but only among those with poorer EF performance. This specific impact on accuracy is consistent with our prior findings showing that certain contextual factors that tax EF resources impact accuracy (but not speed of performance; , and that they deleteriously impact daily functioning (Niermeyer & Suchy, 2020b;Suchy et al, 2019), particularly if they fluctuate from day to day . Given that lack of routine and switching among multiple tasks likely also taxes EF resources (Beuckels et al, 2019;Rubin et al, 2022;Schneider & Anderson, 2010), it follows that it, too, would lead to IADL errors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, accuracy was negatively impacted by high variability in daily busyness, but only among those with poorer EF performance. This specific impact on accuracy is consistent with our prior findings showing that certain contextual factors that tax EF resources impact accuracy (but not speed of performance; , and that they deleteriously impact daily functioning (Niermeyer & Suchy, 2020b;Suchy et al, 2019), particularly if they fluctuate from day to day . Given that lack of routine and switching among multiple tasks likely also taxes EF resources (Beuckels et al, 2019;Rubin et al, 2022;Schneider & Anderson, 2010), it follows that it, too, would lead to IADL errors.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, some contextual factors have a detrimental indirect impact on IADLs via their direct negative impact on EF, whereas others impact IADLs directly , but only among individuals who are vulnerable to such impacts due to pre-existing EF weaknesses. Extensive research supports the mediation aspect of the ConVExA model, demonstrating that (a) EF is vulnerable to a variety of contextual factors, including nonrestorative sleep (e.g., Niermeyer & Suchy, 2020a; Tinajero et al, 2018), sleep deprivation (Lim & Dinges, 2010; Waters & Bucks, 2011), pain interference (Boselie et al, 2016; Buhle & Wager, 2010; Niermeyer & Suchy, 2020a), and engagement in burdensome emotion regulation (Franchow & Suchy, 2017; Niermeyer & Suchy, 2020a,b); and (b) such factors indirectly impact IADLs via contextually induced, temporary decrements in EF (Brothers & Suchy, 2022; Niermeyer & Suchy, 2020b; Suchy et al, 2019). In contrast to the fairly extensive research supporting the mediation aspect of the ConVExA model, thus far only one study has explicitly tested the moderation component of the model (Suchy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, expressive suppression, the other dimension of maternal emotion regulation, did not significantly moderate the relationship owing to the later employment of expressive suppression relative to cognitive reappraisal in the process of emotion regulation (Gross & John, 2003). Previous Western studies found that expressive suppression was generally linked to negative outcomes, such as poorer executive functional performance (Suchy et al, 2019) and lower interpersonal relationship satisfaction (Sasaki et al, 2021). In Chinese culture, however, expressive suppression is more prevalent, such that the negative impact tends to be smaller (Yang et al, 2021; Yuan et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, the DAILIES allowed us to examine whether our tests can predict IADLs prospectively , generalizing from performance assessed at one timepoint to a future behavior at home. In contrast, most research examines concurrent associations between EF measures and IADL tasks (e.g., Alderman et al, 2003; Conti & Brucki, 2018; Frisch et al, 2012; Suchy et al, 2019), potentially confounding results with a third variable shared in space and time, such as experiencing pain (Attridge et al, 2015; Heyer et al, 2000) or not having slept well the night before testing (Fortier-Brochu et al, 2012; Holding et al, 2021; Miyata et al, 2013). Indeed, such contextual factors have an impact on both EF (Berryman et al, 2014; Niermeyer & Suchy, 2020; Tinajero et al, 2018) and IADLs (Hicks et al, 2008; Stamm et al, 2016; Webb et al, 2018), potentially confounding concurrently observed associations.…”
Section: Discussionmentioning
confidence: 99%